2008
DOI: 10.30552/ejep.v1i3.12
|View full text |Cite
|
Sign up to set email alerts
|

Contribución para la validación de la Escala de relaciones entre estudiantes-profesores (STRS versión italiana) en el entorno educativo italiano.

Abstract: La calidad de la relación maestro-alumno es un tema de investigación relativamente reciente, tanto en el contexto nacional, como en el ámbito internacional. Nuestro objetivo es desarrollar y validar el cuestionario Student-Teacher Relationship Scale, instrumento que se propone valorar la calidad de la relación maestro-alumno desde el punto de vista del maestro. La finalidad es, por lo tanto, descubrir la aplicabilidad del instrumento al contexto italiano, analizando las cualidades psicométricas de la escala. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To measure the teacher's perception of the quality of her relationship with the EG pupil, the CG1 and the CG2 pupil, the instrument used was the Student-Teacher Relationship Scale (Pianta, 2001) in the Italian version (Fraire, Longobardi, Prino, Sclavo, & Settanni, in press;Fraire, Longobardi, & Sclavo, 2008). This scale assesses three relational dimensions: Conflict (10 items), Closeness (8 items) and Dependency (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…To measure the teacher's perception of the quality of her relationship with the EG pupil, the CG1 and the CG2 pupil, the instrument used was the Student-Teacher Relationship Scale (Pianta, 2001) in the Italian version (Fraire, Longobardi, Prino, Sclavo, & Settanni, in press;Fraire, Longobardi, & Sclavo, 2008). This scale assesses three relational dimensions: Conflict (10 items), Closeness (8 items) and Dependency (4 items).…”
Section: Methodsmentioning
confidence: 99%
“…Since the 1990s, new theoretical perspectives in education (Bruner, 1990;Lave and Wenger, 1991;Ford and Lerner, 1992;Cole, 1998) have emphasised the relational and contextualistic component of educational systems, and with the studies of Pianta (1999), the teacher-student relationship has become an independent field of investigation in educational psychology. Through various research findings in this area, it has been shown that teacher relationships can affect the quality of learning (Howes and Hamilton, 1992;Pianta, 1999;Darling-Hammond, 2006) and can alter pupils' success-or failure-oriented trajectories (Birch and Ladd, 1996;Fraire et al, 2008;Kuriloff et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they often play a protective role in face of different risks (Sabol and Pianta, 2012). Generally, the student-teacher bond is evaluated on the base of its quality, that is, the extent to which the dyad is characterized by close or conflictual interactions (Fraire et al, 2008;Sabol and Pianta, 2012). Following a social learning framework (Bandura, 1971(Bandura, , 1986, children learn and behave through modeling and imitation of others, as well as through vicarious experiences, particularly when the role models are socializing agents (e.g., teachers and parents) or are taken as positive models.…”
Section: The Role Of the Relationship With Teachersmentioning
confidence: 99%
“…The Student-Teacher Relationship Scale (Pianta, 1994; Italian version by Fraire et al, 2008) was adopted to investigate how teachers perceived their relationship with each pupil. The instrument consists of three subscales: Closeness, Conflict, and Dependence.…”
Section: The Quality Of Student-teacher Relationshipmentioning
confidence: 99%